Coating studies of intra-ocular lens with drug delivery - Wu, Shiling. (2013)
Current post-operative regime of cataract surgery involves a short course of antibiotic eye drops to prevent endophthalmitis. To replace current administration of eye drops, biodegradable attachment ring with drug eluting feature is fabricated using spray coater; with a customised mandrel to produce even hooks that can be clipped onto the intraocular lens implant. In vitro drug release study has shown that ring with sandwich configuration is capable of a drug release of above 0.3% bioavailability of levofloxacin in eye drop for a period of more than 2 weeks. In vitro degradation has shown that the weight average molecular weight of PLC with 15% levofloxacin has similar degradation profile as PLC without levofloxacin.